Comparative Descriptors of Applicants and Graduates of Online and Face-to-Face Master of Science in Nursing Programs. - Cameron, Nancy G. (Nursing Education Perspectives (National League for Nursing), 2013)
AIM Proper advisement of students about their programs of study requires knowledge of the applicants and confidence that the recommended curricula will lead to success via graduation and certification. BACKGROUND Two important strategies to deliver master of science in nursing (MSN) curricula include online and face-to-face (F2F) formats. METHOD A nonexperimental, descriptive study of archival data was used to examine and compare the characteristics of F2F and online MSN applicants, admitted students, and graduates as well as family nurse practitioner (FNP) certification pass rates at one eastern Tennessee college of nursing. Administration and FNP concentrations were studied. RESULTS The average applicant grade point average (GPA) was higher for the F2F format but no difference in the average admission GPA was found between formats. The online students had more years of RN experience than the F2F students. CONCLUSION No significant difference was found between graduating GPAs or FNP certification pass rates.